2016
DOI: 10.1186/s13046-016-0311-5
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of histone demethylase KDM5B inhibits cell proliferation of hepatocellular carcinoma by regulation of cell cycle checkpoint proteins p15 and p27

Abstract: BackgroundKDM5B is a jmjc domain-containing histone demethylase which remove tri-, di-, and monomethyl groups from histone H3 lysine 4 (H3K4). KDM5B has been determined as an oncogene in many malignancies. However, its expression and role in hepatocellular carcinoma (HCC) remain unknown.MethodsWe detected the expression of KDM5B in HCC tissues and cell lines. Cell proliferation was performed to reveal the role of KDM5B depletion on HCC cells both in vivo and in vitro. Flow cytometry was used to analyze the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 43 publications
5
48
0
Order By: Relevance
“…On the other hand, knockdown of KDM5B in hepatocellular carcinoma cells (HCCs) inhibits cell proliferation via cell cycle arrest at the G1/S phase. In this case, KDM5B induces the expression of key cell regulatory genes (e.g., p15 and p27) by removing the methylation mark of histone H3K4me3 from their promoters [139]. Consistent with these data, KDM5B overexpression in HCCs increases proliferation, EMT, migration, and invasion in vitro, and enhances tumorigenic and metastatic capacities in vivo [137].…”
Section: The Kdm4 Cluster (Jmjd2 Subfamily)supporting
confidence: 72%
“…On the other hand, knockdown of KDM5B in hepatocellular carcinoma cells (HCCs) inhibits cell proliferation via cell cycle arrest at the G1/S phase. In this case, KDM5B induces the expression of key cell regulatory genes (e.g., p15 and p27) by removing the methylation mark of histone H3K4me3 from their promoters [139]. Consistent with these data, KDM5B overexpression in HCCs increases proliferation, EMT, migration, and invasion in vitro, and enhances tumorigenic and metastatic capacities in vivo [137].…”
Section: The Kdm4 Cluster (Jmjd2 Subfamily)supporting
confidence: 72%
“…This effect is maintained in hepatocellular cancer [6] and is also described in lung cancers via JARID1A [46]. JARID1A and JARID1B-mediated repression of other cdk inhibitors is also reported, including effects on p15, p16, and p21 [6, 12, 48, 49]. It remains unclear what contextual determinants dictate whether JARID1 proteins drive G 1 -S progression or promote arrest and senescence.…”
Section: Jarid1 Contribution To Cancer Progressionmentioning
confidence: 99%
“…JARID1B amplification and overexpression are strongly associated with poor prognosis in hormone receptor-positive tumors and drive a luminal-type gene expression profile [4]. It is also upregulated in numerous other cancers including prostate [5], hepatocellular [6], and ovarian [7]. Despite low JARID1B levels in melanomas relative to benign nevi [8], these cancers contain a fraction of cells where high JARID1B expression confers stem cell-like molecular and functional traits [9], drives oxidative metabolism, and increases drug resistance [10].…”
Section: Jarid1 Proteins In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that lncRNAs contribute to cancer cell phenotypes by silencing tumour suppressors or activating oncogenes . In addition, many cell cycle‐related genes (including p15, p21, p27 and KLF2) act as tumour suppressors in various cancers by inhibiting the activity of kinases involved in the G1/S transition . Our previous studies have demonstrated that lncRNA BANCR (BRAF activated non‐coding RNA) promotes CRC cell proliferation partly by down‐regulating p21 expression …”
Section: Introductionmentioning
confidence: 99%